74‐1: 31″ Flexible Printed OLED TV Display Technology: It's TV Mobiles. Issue 1 (28th June 2022) - Lee, Jueng Gil (James); Gao, Zhuo; Fu, Dong; Yan, Xiaolin
Abstract : The flexible printed OLED TV display technology will be able to create new application market, such as rollable/foldable TV, in the future. It's TV Mobiles. Recently, the TCL (Guangdong Juhua Printed Display Technology Ltd. Co, TCL CSOT & TCL Corporate Research) has successfully demonstrated the 31″ FHD flexible printed OLED TV in CES 2020. The product is fabricated by ink jet printing technology with top emission OLED device architecture, advanced encapsulation technology and is driven by IGZO oxide TFT B/P technology. The panel performance of 31″ flexible printed OLED TV has continuously improved drastically after demonstration at CES based on optimization of top emission OLED device architecture including printing OLED material development, MURA free printing technology, Oxide TFT B/P technology and advanced thin film encapsulation technology. The RGB device performance of 31" FHD flexible printed OLED TV has high current efficiency and long‐life time, R:(0.68, 0.32), 46.3cd/A, LT95>8khrs@1knits, G:(0.28, 0.70), 115.5cd/A, LT95>6khrs@1knits, B:(0.13, 0.062), 5.35cd/A, LT95 >0.35khrs@1knits respectively. It is getting closer and closer to meet the commercial requirement of flexible OLED TV target specification. The technical challenges of 31″ FHD flexible printed OLED TV are also identified. In this paper, the technology development status and technical challenges are discussed